Sources and Distribution of N-Alkane and Polycyclic Aromatic Hydrocarbons in Selected Locations in Peninsular Malaysia - Bakhtiari, Alireza Riyahi (2009)
Distribution and sources of perylene have not been thoroughly investigated and are therefore not well understood in the tropical environment. This study focusses on the distribution pattern and source identification of aliphatic hydrocarbons and polycyclic aromatic hydrocarbons particularly perylene. Surface sediments, suspended particulate matter, sediment core samples, different compartments of termite nests (Macrotermes gilvus) and the surrounding soils and plants were collected from the Klang River, Langat River, Chini Lake and in the campus of Universiti Putra Malaysia, respectively. Alkanes and perylene concentrations were significantly different in new and old fungus combs particularly in large termite nests. There are also significant differences between alkyl-C, neutral carbohydrate, aromatic rings of lignin and chitin concentrations in new and old fungus combs. The levels of nC31/ (nC27+nC29+nC31) ratios revealed that new and old fungus combs may receive more contribution from grass waxes relative to tree and shrub waxes. Termites M. gilvus and woody plants are sources of perylene in the tropical environment. The distribution patterns of n-alkanes and PAHs suggest that the upstream stretch of the Langat River receives greater inputs of these compounds when compared to the downstream stretches. This may be due to the fact that industrial areas are concentrated in Kajang and Bangi towns. Lower and medium molecular weight PAHs and n-alkanes were dominant in suspended particulate matter, whereas higher molecular weight PAHs and nalkanes were dominant in surface sediments. Results of diagnostic ratios indicate mixed petrogenic and pyrogenic sources with predominance of pyrogenic inputs for 18 PAHs and perylene in Langat River sediments. The data collected from Klang River sediments show that petrogenic inputs were predominant at all of the stations investigated. In Lake Chini sediment core samples, perylene concentrations were high in the top layers (0-12cm) and increased with increasing depths. Analysis of variance (ANOVA) and least significant difference (LSD) tests revealed that there were significant differences (p<0.05 at the 95% confidence level) in TOC-normalized perylene concentrations between the top layers and the bottom layers of the sediment core samples. This can be attributed to different sources of perylene. The results of analysis of critical ratios of perylene, such as perylene/total PAHs, perylene/panta-aromatic isomers of perylene and pyrene/perylene indicate biological sources in the top layers and in situ formation of perylene in the bottom layers. These results are consistent with the results for n-alkane concentrations and suggest that Lake Chini sediments are highly affected by terrestrial vascular plants. Source identification of metals exhibits the predominance of natural inputs for Cu and Zn in the top layers and anthropogenic inputs for Cu, Zn, Pb, and Cd in the bottom layers of the Lake Chini sediment profiles. Results of correlation analysis among the metals and between each metal and Σ19PAHs, perylene and perylene/TOC indicate significant positive correlations between PAHs and Cu concentrations (r = 0.79, p = 0.002), Zn concentrations (r = 0.73; p = 0.007) and Pb concentrations (r = 0.68; p = 0.016), respectively. There was no significant correlation found between PAHs and Ni and Cd (r = 0.53; p = 0.077), (r = 0.57; p = 0.051). Furthermore, perylene and perylene/TOC were significantly correlated with Cu, Zn and Pb. A possible explanation for these results may be ascribed to enzymatic activities of microorganisms. Cu and Zn are essential elements in many metallo-enzyme processes for microorganisms. In addition, Pb can be used by anaerobic bacteria during the methylation process using methylase enzymes. It is concluded that perylene is formed in termite (M. gilvus) nests. It accumulates in new fungus comb. High concentrations of aromatic rings of lignin as a precursor of perylene are found in new fungus combs. It is postulated that perylene is supplied to the river as a result of the heavy and frequent rains in the tropical climate. The fact that perylene was found in abundance in the top layers of the sediment core samples from Lake Chini under aerobic conditions is in contrast with the results of other studies elsewhere. A minor concentration of perylene is believed to be degraded into derivative isomers which are found in old fungus combs and also in Lake Chini sediments.